(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1993)
It is shown that if K is a Grothendieck compact space, then K admits a strictly positive measure if and only if there exists a linear bounded one-to-one operator T:C(K) → c_0(Γ)